Cyberterrorism: four Reasons for Its Absence—So Far - Jacobsen, Jeppe Teglskov (Perspectives on terrorism, 2022)
Why has cyberterrorism (still) not happened? This article revisits two existing explanations and adds two novel ones. First, developing fear-inducing destructive cyberattacks is more difficult and involves more uncertainty in terms of producing harmful effects than conventional terrorist attacks. Second, cyberattacks rarely produce spectacular imagery. Since cyberattacks with the potential to cause fear do not necessarily require as high technical barriers of entry as an imagined cyber 9/11, the author adds two additional explanations to better understand the absence of cyberterrorism. Third, a corporal explanation: Violent bodies most often come into being through memetic practices of other violent figures and artefacts but the hacker’s subjectivity is different from the typical non-state terrorist. Rather than through violence, the thrill of hacking emerges after having stared at endless lines of code, when a technical puzzle is solved, and access to an IT system is achieved. And fourth, a social explanation: it is difficult for prospective cyberterrorists to build the necessary amount of trust online. Based on these four explanations, the article sketches the likely characteristics of a future cyberterrorist. If we are to experience cyberterrorism from non-state actors, we will most likely face an antisocial Unabomber-like figure who has acquired the necessary technical knowhow independently, while not being attracted to a violent spectacle or to violent imitations of a jihadi or right-wing corporality.